PENYELESAIAN KREDIT MACET MELALUI LEMBAGA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) - Dini Syakina Siregar; Ramli Siregar; Windha windha (Universitas Sumatera Utara, 2013)
To enter the era of globalization and face the ever-growing national economy moving fast, the banking sector is one of the sectors that should be developed and fully utilized to realize the income distribution. Terms of the law, the presence or absence of bad loans that hit a bank, does not result in a shift or change in the legal relationship between the creditor banks on the one hand and customers who have bad credit debtors on the other. The formulation of the problem that is discussed in this paper is on how the handling of bad loans in the banking environment, and discussed the relationship between the bagimanakah Suspension of Payment (PKPU) with bad credit, and at the end of this thesis is discussed more about how loan resolution through non Suspension of Payment (PKPU). Handling bad debts in the banking environment is done in two ways: first, preventive efforts in handling bad debts by banks and secondly, the bank will undertake repressive measures to rescue the rescheduling loans (rescheduling), the only change in credit terms regarding schedule payment and / or duration. Relationships that exist between PKPU with bad credit is PKPU can be done either to avoid bad credit. This is evident from the characteristic PKPU as stated in Chapter III Section 222-294 UUK. Loan resolution through PKPU can be done by both the debtor and creditor (bank) in order to propose a peace plan that includes an offer to pay part or all of the debt to the creditor with the following steps. Whereas in the case of PKPU petition filed by a creditor, the court must grant the petition immediately PKPU no later than twenty days from the registration of the application. The court must appoint a supervisory judge and appoint one or more administrators. Commercial Court decision on temporary PKPU is valid for a maximum of forty days and after that it should be decided whether the PKPU can continue to be a PKPU regularly in accordance with Article 225 paragraph (3) Labor Law and PKPU; PKPU next stage is fixed, after a specified delay while debt repayment obligations, the Commercial Court through official must call the debtor and the creditor in question to appear in a hearing held not later than forty-five days since the enactment of the decision PKPU while. In the trial will decide whether it can be given PKPU be fixed with a view to allowing debtors, trustees, and creditors to consider and approve peace. The PKPU can be approved if it is still in accordance with Article 229 Paragraph (1) Labor Law and PKPU. Keywords: Kredit, penyelesaian, Penundaan Kewajiban Pembayaran Utang (PKPU).